The Effect of Locus of Control, Learning, and Adversity Quotient towards Micro Business Success (Study on Entrepreneurship under Foster Group of the Banjarmasin Regional Government) - Titien Agustina; Wida Gerhana; Sulaiman Sulaiman (Center for Journal Management and Publication, 2020)
Micro, small and medium entrepreneurs are the economic drivers at the lower levels and they generally rely on the ability of human resources. Nevertheless, they will be extraordinary if all their potential is nurtured, explored and developed because the factors that trigger success are not only determined by external conditions, but also internal conditions. Among the internal factors that spur one's success are locus of control, learning, and adversity quotient. This study aims to examine the partial and simultaneous effects of locus of control, learning, and adversity quotient on business success. The research respondents were a foster group of entrepreneurs under Banjarmasin, total 1881 people. With the Slovin formula, 100 respondents appear. The results of the study showed partially that the t value of the effect of locus of control on business success was 3.046. T value calculated the effect of learning on business success was 2,150. T value calculated the effect of adversity quotient on business success was 4.924. Thus, adversity quotient had the most dominant influence on business success. The correlation coefficient of 51,944 and the probability value between variables of 0,000 indicate a significant effect between locus of control, learning, and adversity quotient on business success simultaneously. Finally, it was found that R square 0.619 means 69.1% where business success can be explained by the locus of control, learning, and adversity quotient variables; the remaining 30.9% was explained by other factors. The research findings that the guidance provided must be ongoing, not only with training, but also need to foster mental and spiritual change as a true entrepreneurship through strong locus of control, continuous learning, and high adversity quotient.